THE NATURE AND ORIGIN OF ULTRAMAFIC LAMPROPHYRES: ALNöITES AND ALLIED ROCKS - Rock N.M.S. (My University, 1986)
Ultramafic lamprophyres (UML) are rare but widespread, hypabyssal rocks, rich in K, Mg, Cr, Ni, Sr, Ba, REE, and volatiles, containing less Si and more Ca than other silicate igneous rocks, and grading into carbonatites. They carry phenocryst combinations of olivine (Fo92–72), phlogopite (rich in Ti, Fe3+ , Ba or F), Al-Ti-(Fe3+ and richteritic to eckermannitic amphiboles. Groundmasses include Ca-Fe-Mg-carbonates (?partly primary), feldspathoids, Ca-Fe-Ti-Zr-garnets, soda-melilite, monti cellite, Mg-Mn-ilmenite, perovskite, serpentine, Fe- Mg-Ti-Mn-Cr-Al-spinels ± glass. Megacrysts include (?cognate) salitic pyroxenes, phiogopites or Ti-hastingsites, and more rarely, xenocrystic Cr-Ti-pyrope, orthopyroxenes and diopsides. Xenoliths include spinel and/or garnet-lherzolites, dunites, and phlogopite±amphibole-bearing pendotites. UML are readily distinguished from kimberlites by petrological association (e.g. with ijolites), geochemistry (e.g. lower Mg, higher Ca, P), texture (e.g. lack of two olivine generations) and mineralogy (e.g. presence of groundmass feldspathoids ± melilite). UML are distinguished also from melilitites by lower Si, Al, Na, higher Ca, K, P; more abundant primary carbonate, phiogopite and amphibole; and by lack of groundmass olivine and phenocryst melilite. Closer extrusive equivalents of UML may however occur among ankaratrites. The most common UML types are alnöite (melilite-rich) and aillikite (melilite-free, carbonate-rich). Aillikites are compositionally closer to carbonatites than alnOites. Rarer types include poizenite (melilite + feldspathoids), ouachitite (feldspathoids + carbonates) and damkjernite (feldspathoids + carbonates+ < 10 per cent alkali feldspars). UML form localized dyke-swarms or diatreme-clusters, mainly related to continental rifting, and may represent parent magmas for coeval carbonatite complexes. Their additional occurrence in an oceanic setting, their mantle xenolith content, and their high mg, Cr and Ni, together suggest that many of them are primary, mantle-derived magmas, generated at depths between those of melilitites and kimberlites (c. 100–150 km), but at higher CO2 pressures than melilitites. Other UML, however, have been extensively modified from primary compositions by fractionation, accumulation, or interaction with alkali+volatile-rich fluids.